Reproductive aspects of the Atlantic angel shark Squatina dumeril in the southern Caribbean Sea. Issue 4 (12th September 2017) - Tagliafico, A.; Rangel, S.; Broadhurst, M. K.
Abstract : The maturity and reproduction of the Atlantic angel shark Squatina dumeril were assessed using 77 females (29·2–110·4 cm total length; L T ) and 269 males (58·7–108·2 cm L T ) harvested by artisanal gillnetters off Venezuela. The biased sex ratio implied segregation or sex‐specific gear selectivity. Based on the development of the reproductive tract, 50% L T at sexual maturity ( L T50, mean ±s.e .) for females and males were estimated at 86·14 ± 0·64 and 81·55 ± 0·12 cm, respectively. Uterine fecundity ranged between one and six and with a maximum embryo size of 25·7 cm L T . Gravid females were observed from August to December, including those close to parturition and while the gestation period was not confirmed, the size of ovarian follicles among some specimens implied protraction. The low fecundity of the species supports close monitoring of catches.